DDCI-01, a novel long acting phospdiesterase-5 inhibitor, attenuated monocrotaline-induced pulmonary hypertension in rats - Ailing Li; Zhongkai Zhu; Yangke He; Qian Dong; Dianyong Tang; Zhongzhu Chen; Wei Huang (Pulmonary Circulation, 2020)
Pulmonary arterial hypertension is a progressive, malignant heart disease, characterized by pulmonary arteriole remodeling and increased pulmonary vascular resistance, which eventually leads to right heart failure. This study sought to evaluate the effects of a novel long-acting phospdiesterase-5 inhibitor, namely DDCI-01, as an early intervention for monocrotaline-induced pulmonary hypertensive rats. To establish this model, 50 mg/kg of monocrotaline was intraperitoneally injected into rats. At Day 7 after monocrotaline injection, two doses of DDCI-01 (3 or 9 mg/kg/day) or tadalafil (at 3 or 9 mg/kg/day) were intragastrically administered. The rats were anesthetized with pentobarbital for hemodynamic and echocardiographic measurements, at Day 21 after monocrotaline injection. Compared to the monocrotaline group, DDCI-01 at 3 and 9 mg/kg/day (P) reduced the mean pulmonary arterial pressure (mPAP), right ventricular systolic pressure, right ventricular transverse diameter, pulmonary arterial medial wall thickness (WT%), and right ventricle hypertrophy. However, no significant difference in the indices mentioned as above was found between DDCI-01 (3 mg/kg/day) and tadalafil (3 mg/kg/day). In addition, DDCI-01 at 9 mg/kg/day resulted in lower mPAP and WT%, as well as higher cyclic guanosine monophosphate levels in the lung and plasma compared with the same dose of tadalafil (9 mg/kg/day) (all P  < 0.05). These findings suggested that DDCI-01 improved monocrotaline-induced pulmonary hypertension in rats, and a dose of DDCI-01 of 9 mg/kg/day might be more effective than the same dose of tadalafil in monocrotaline-induced pulmonary hypertension in rats.